(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Physique of science hard the body mechanic properties , mechanical stress relative to lengthen dependence in explanation very efficient method is considered Mechanic voltage relative to prolong connection graph student and in explaining to students much to difficulties occurs . This is the method using of students creative thinking by increasing good to understanding have to be provides. Physics in science applied another of the methods different side this method students with the help of animated graphics seeing thinking the ability increases . Offer The so- called ―Dinosaur‖ is innovative method foreign in analogues there is it’s not . Such method Uzbek topics that are not found in the literature graph which explains in a way methods there is but they are this the subject in explanation efficient it’s not . Current at the time Physics science to teach according to work developed methods using physics of science some from departments in use difficulty gives birth Eliminate these difficulties reach for new innovative methods need will , I suggest which method of physics mechanics in the department hard of the body mechanic properties on the subject of mechanical stress relative to lengthen connection The graphic of ― dinosaur ‖ is innovative method in explaining using if used very big efficient and good quality teaching enable creates [1]. Mechanic voltage relative to lengthen connection in the graph hard body strength check as a result received is a graph.